1997
DOI: 10.1143/jjap.36.3644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of O 2/Ar Ratio and Annealing on the Properties of (Ba,Sr)TiO 3 Films Prepared by RF Magnetron Sputtering

Abstract: The magnetic circular dichroism of KCI:TI and KI:T1 has been measured after x-irradiation at 77 K. The results support earlier assignments of some optical absorption bands in the irradiated crystals to TI0 and TIZ+ ions; these valence states result from the capture of electrons and holes by TI+ ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…According to J. Lee et al, the grain size of BST films increased as the O 2 content of the sputtering gas increased [18]. In our previous work, it was found that the dielectric constant and tunability increased with the increasing grain size [16].…”
Section: Sputtering Gasmentioning
confidence: 77%
“…According to J. Lee et al, the grain size of BST films increased as the O 2 content of the sputtering gas increased [18]. In our previous work, it was found that the dielectric constant and tunability increased with the increasing grain size [16].…”
Section: Sputtering Gasmentioning
confidence: 77%
“…Both pores and protrusions seem to contribute to the detected leakage currents at a high bias of 6 V. The surface morphology of the STO/RuO 2 film grown at 500 1C is rougher than those of the STO/Pt and STO/LNO films. The increase in the leakage currents of the STO/RuO 2 film may be associated with the rough structure between the insulator and the bottom electrode [20]. Fig.…”
Section: Resultsmentioning
confidence: 97%
“…11 The leakage current of the dielectric oxide which increases with the roughness of the interface between the insulator and the bottom electrode has been reported. 16 The above SIMS analysis reveals that the relatively rough interface of BFO/Pt at 550°C may also be responsible for the poor electric performance. A trace amount of leakage spots was found for the BFO/Pt film grown at 450°C at a bias of 2 V. As the bias is increased to 4 V, the original leaky spots that were formed at 2 V dilated because increasing the applied voltage broadened the tunneling area of the electrons, increasing the lateral dimensions of the current spots.…”
Section: Methodsmentioning
confidence: 93%